Blending Bytes, Blazing Boundaries: Unraveling the Enthralling Expedition of EFL Undergraduate Students' Motivational Dynamics in the Revolutionary Realm of Blended Learning - Moh Ruzin; Bambang Yudi Cahyono; Nanang Zubaidi (Language Circle: Journal of Language and Literature, 2026)
Blended learning has emerged as a prominent teaching approach in the post-pandemic era, particularly in higher education. This study investigated students' motivation levels on blended learning environments. Using mixed-method design, data were collected from 101 third-semester English Language Education students at a public university in Malang, Indonesia. Participants who had participated in both in-person and online learning completed online questionnaires and semi-structured interviews. The data obtained from the questionnaires were analyzed using formula from Sugiyono (2015) to derive percentage data. Then, semi- structures interviews transcripts were analyzed using the interactive qualitative data analysis model, such as data condensation and display, conclusion and verification. The findings of this study indicated that students expressed primarily high level of motivation in blended learning environments. Further, their motivation levels were influenced by various factors, including clarity of materials, technology working properly, prior learning experiences, and the physical and emotional environment. While the findings express the potential for blended learning to foster learner autonomy and learner motivation, it should be noted that the study was limited by sample size, students’ experiences, and self-reported data. In turn, future research should include contexts and methods that involve more participants to increase generalizability and further understanding of learner engagement in blended learning environments.